Post-Hatch Performance of Broilers Following Hypoxic Exposure During Incubation Under Suboptimal Environmental Temperature - Haron, A.; Shinder, D.; Ruzal, M.; Druyan, S. (Frontiers in Physiology, 2022)
The modern broiler is selected to exploit its full genetic potential, to sustain a rapid growth rate, and to lower the feed conversion ratio (FCR). Recently reported reductions in FCR have been associated with augmented tissue formation at the expense of physiological functions such as thermoregulation. In turn, modern broilers exhibit a relatively low capability to balance energy expenditure under suboptimal ambient temperature. Hypoxic conditions at late incubation stages play a role in reforming metabolic plasticity. This work examined the effect of exposure to 12-hour hypoxia (12H; 17% O2) for three consecutive days (from E16 through E18), or continuous hypoxia exposure for 48 hours (48H), from E16 through E17, as compared to standard incubation (21% O2) on post-hatch performance of broilers maintained under suboptimal ambient temperatures (cold, hot and diurnal cyclic ambient temperature). 12H chicks kept under hot ambient temperature had significantly lower body temperature (Tb) as compared to the control chicks. On day 42, both 12H and 48H chicks grown in the cyclic temperature room had significantly lower Tbs than controls. In parallel, from week 4, onward, 12H chicks had a significantly lower FCR than controls, and the 48H chicks demonstrated a lower FCR from week 5 and on. 12H and 48H broilers maintained under diurnal cyclic ambient temperature, exhibited significantly greater relative breast muscle weight, and a similar pattern was found in hypoxic broilers raised under standard and hot ambient temperatures. Hypoxic manipulation affects and create an adaptive bias in allocating metabolic energy between maintenance and growth, thus resulting in improved broiler performance, thermoregulation, and rearing under suboptimal environmental temperature.